(untitled) (Agroindustrial Science, 2022)
In the present investigation, the hepatoprotective effect of a powder mixture of leaves of Gentianella alborosea (Gilg) Fabris, Cynara scolymus, Berberis vulgaris, Peumus boldus, Taraxacum officinale roots, and vitamins B6 and B12 (PROTHEPA®) was studied in Rattus norvegicus. Sprague Dawley with paracetamol-induced liver intoxication. In the experiment, 25 female rats were randomly distributed into five groups, G1: physiological serum (SF) 4 mL/kg; G2 (negative control): SF 4 mL/kg + paracetamol 400 mg/kg; G3 (positive control): Silymarin 100 mg/kg + paracetamol 400 mg/kg; G4: PROTHEPA® mixture 100 mg/kg + paracetamol 400 mg/kg; and G5: PROTHEPA® mixture 500 mg/Kg + paracetamol 400 mg/kg. Biochemical analyzes were performed to determine the liver profile (glutamic oxalacetic transaminase (GOT), glutamic pyruvic transaminase (GTP), total bilirubin (BT), and total protein (PT)), as well as pathological evaluations. The results showed that G2 presents a significant increase in TGP (80.20 ±1.3), BT (0.39 ± 0.23), and a significant reduction in PT (4.82 ± 0.46). As for G3, G4 and G5; all tests remained within normal values, similar to G1. These results demonstrate that the PROTHEPA® mixtures of 100 mg/kg and 500 mg/kg have a hepatoprotective effect, which is corroborated by the anatomo-pathological evaluations.